Exploring the human chorionic gonadotropin induced steroid secretion profile of mouse Leydig tumor cell line 1 by a 20 steroid LC-MS/MS panel. Issue 229 (May 2023) - Fanelli, Flaminia; Magagnoli, Matteo; Mezzullo, Marco; Lispi, Monica; Limoncella, Silvia; Tommasini, Alessia; Pelusi, Carla; Santi, Daniele; Simoni, Manuela; Pagotto, Uberto; Casarini, Livio
Abstract: The canonical androgen synthesis in Leydig cells involves Δ5 and Δ4 steroids. Besides, the backdoor pathway, eompassing 5α and 5α, 3α steroids, is gaining interest in fetal and adult pathophysiology. Moreover, the role of androgen epimers and progesterone metabolites is still unknown. We developed a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for measuring 20 steroids and used it to investigate the steroid secretion induced by human chorionic gonadotropin (hCG) in the mouse Leydig tumor cell line 1 (mLTC1). Steroids were extracted from 500 µL supernatants from unstimulated or 100 pM hCG-exposed mLTC1 cells, separated on a Luna C8 100 × 3 mm, 3 µm column, with 100 µM NH4F and methanol as mobile phases, and analyzed by positive electrospray ionization and multiple reaction monitoring. Sensitivity ranged within 0.012–38.0 nmol/L. Intra-assay and inter-assay imprecision were < 9.1% and 10.0%, respectively. Trueness, recovery and matrix factor were within 93.4–122.0, 55.6–104.1 and 76.4–106.3%, respectively. Levels of 16OH-progesterone, 11-deoxycortisol, androstenedione, 11-deoxycorticosterone, testosterone, 17OH-progesterone, androstenedione, epitestosterone, dihydrotestosterone, progesterone, androsterone and 17OH-allopregnanolone were effectively measured. Traces of 17OH-dihydroprogesterone, androstanediol and dihydroprogesterone were found, whereas androstenediol, 17OH-pregnenolone, dehydroepiandrosterone, pregnenolone and allopregnanolone showed no peak. hCG induced an increase of 80.2–102.5 folds in 16OH-progesterone, androstenedione and testosterone, 16.6 in dihydrotestosterone, 12.2–27.5 in epitestosterone, progesterone and metabolites, 8.1 in 17OH-allopregnanolone and ≤ 3.3 in 5α and 5α, 3α steroids. In conclusion, our LC-MS/MS method allows exploring the Leydig steroidogenesis flow according to multiple pathways. Beside the expected stimulation of the canonical pathway, hCG increased progesterone metabolism and, to a low extent, the backdoor route. Highlights: Twenty steroids are simultaneously measured by a novel validated LC-MS/MS assay. Androgens and progesterone metabolites are secreted by unstimulated mLTC1. Human chorionic gonadotropin massively activated the canonical pathway. Human chorionic gonadotropin activated the backdoor pathway to a low extent. Human chorionic gonadotropin moderately activated progesterone metabolism.